Selective Transport of Silver(I) Ion Through Polymer Membranes Containing Thioether Donor Macrocycles as Carriers - A. Nezhadali; M. Akbarpour (E-Journal of Chemistry)
The Preparation of polymer membrane and it's selectivity to silver(I) ion from an aqueous solution containing seven metal cations, Co(II), Ni(II), Cu(II), Zn(II), Ag(I), Cd(II) and Pb(II), was studied. The source phase contained equimolar concentrations of the above mentioned cations with the source and receiving phases being buffered at pH 5.0 and 3.0 respectively. The effect of variation in the number of the macrocyclic sulfur atom donor set anssd the size of ring 9 and 16 member macrocycles on transport efficiency is presented. Silver(I) ion transport occurred (at 25°C) from the aqueous source phase across the polymer membrane (derived from cellulos triacetate) containing ligands 9-membered, S3-donor and16-membered S4-donor macrocycles as the ionophors in separate experiments into the aqueous receiving phase. Clear transport selectivity for silver(I) ion was observed using both thioether donor macrocycles. The efficiency of transport rate for silver(I) ion with using 9-membered S3-donor macrocycle as carrier was better than 16-membered S4-donor .